CN116986830B - Low-calcium silicate cement clinker, cement and preparation method thereof - Google Patents
Low-calcium silicate cement clinker, cement and preparation method thereofInfo
- Publication number
- CN116986830B CN116986830B CN202311058401.8A CN202311058401A CN116986830B CN 116986830 B CN116986830 B CN 116986830B CN 202311058401 A CN202311058401 A CN 202311058401A CN 116986830 B CN116986830 B CN 116986830B
- Authority
- CN
- China
- Prior art keywords
- raw materials
- low
- clinker
- cement clinker
- cement
- Prior art date
- Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
- Active
Links
Classifications
-
- C—CHEMISTRY; METALLURGY
- C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
- C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
- C04B7/00—Hydraulic cements
- C04B7/24—Cements from oil shales, residues or waste other than slag
- C04B7/26—Cements from oil shales, residues or waste other than slag from raw materials containing flue dust, i.e. fly ash
-
- C—CHEMISTRY; METALLURGY
- C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
- C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
- C04B7/00—Hydraulic cements
- C04B7/02—Portland cement
- C04B7/04—Portland cement using raw materials containing gypsum, i.e. processes of the Mueller-Kuehne type
-
- C—CHEMISTRY; METALLURGY
- C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
- C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
- C04B7/00—Hydraulic cements
- C04B7/14—Cements containing slag
- C04B7/147—Metallurgical slag
-
- C—CHEMISTRY; METALLURGY
- C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
- C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
- C04B7/00—Hydraulic cements
- C04B7/24—Cements from oil shales, residues or waste other than slag
-
- C—CHEMISTRY; METALLURGY
- C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
- C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
- C04B7/00—Hydraulic cements
- C04B7/36—Manufacture of hydraulic cements in general
Landscapes
- Chemical & Material Sciences (AREA)
- Engineering & Computer Science (AREA)
- Ceramic Engineering (AREA)
- Materials Engineering (AREA)
- Structural Engineering (AREA)
- Organic Chemistry (AREA)
- Curing Cements, Concrete, And Artificial Stone (AREA)
Abstract
The invention discloses a low-calcium silicate cement clinker, cement and a preparation method thereof, wherein the cement clinker comprises the following mineral components :C3S:5~20%,C2S:50~60%,C6AF2:10~20%,C3A:0-7%,C4A3$:0.1~15%. by mass percent, and further improves the later-stage performance of the clinker, and meanwhile, the early strength formed by rapid hydration of C 4A3 $ can make up for the problem of insufficient early hydration activity of the clinker caused by the improvement of the content of C 2 S, so that the cement has good performance development in the early, middle and later stages.
Description
Technical Field
The invention relates to the field of building materials, in particular to low-calcium silicate cement clinker, cement and a preparation method thereof.
Background
The China is a large country for cement production and cement carbon emission, and the cement industry is a second large carbon emission industry in the industrial field of China due to large yield, and faces huge carbon emission reduction pressure. Portland cement is the dominant product in the cement industry in China, and 0.97t of CO 2 is discharged per 1t of cement production on average. The main mineral compositions of the silicate cement clinker comprise tricalcium silicate (C 3 S), dicalcium silicate (C 2 S), tetracalcium aluminoferrite (C 4 AF), tricalcium aluminate (C 3 A) and the like. Wherein, C 3 S calcium content is highest, carbon emission is high, and the content of C 3 S needs to be greatly reduced, so that novel low-calcium silicate cement clinker is developed to reduce carbon emission in the cement industry.
The mineral components of the high-strength silicate cement clinker containing calcium sulfoaluminate disclosed in the patent of 201310138543.5 comprise 0.5-3% of C3S 50~75%,C2S 2~25%,C4AF 2~8%,C3A 2~25%,C4A3$ 2~9%, free calcium oxide (f-CaO), 1-6% of periclase (MgO) and 0-3% of gypsum (CaSO 4). In the patent, a twice calcination procedure is used, portland cement clinker is calcined at 1400-1500 ℃, the obtained clinker is heated to 1000-1300 ℃ for twice calcination, and quenched to obtain the clinker, wherein the strengths of the clinker 3d and 28d are 42-44 MPa and 65-72 MPa respectively. The invention introduces C 4A3 $ into the silicate cement clinker by using a two-step firing method, and can improve the compressive strength of the clinker. However, the clinker C 3 S content is higher, so that the carbon emission is more, and the secondary sintering process further consumes a large amount of energy.
The invention patent with the application number 202210843960.9 provides a high-sulfur-resistant silicate cement clinker, wherein the clinker mineral composition comprises 10-23% of C 3S 35~60%,C2S 15~35%,C3A 0~7%,C6AF2, and the clinker is prepared by heat preservation for 30-40 min at 1350-1420 ℃. The introduction of C 6AF2 obviously improves the sulfate erosion resistance of the cement clinker, and can reduce the cost and energy consumption of cement production. But it only focuses on sulfur resistance and cannot guarantee early and later strength properties required for engineering construction.
Disclosure of Invention
The invention provides a low-calcium silicate cement clinker, cement and a preparation method thereof, which are characterized in that the later strength of the clinker is ensured by designing high silicon content in the silicate cement clinker, the wear resistance of the clinker is improved by designing high iron content, sulfur is introduced in the sintering process of the clinker, so that the sulfur in the clinker exists in a form of C 4A3 $, and the early performance of the clinker is ensured.
The invention adopts the technical scheme that the low-calcium silicate cement clinker comprises the following mineral components in percentage by mass :C3S: 5~20%,C2S: 50~60%,C6AF2: 10~20%,C3A: 0-7%,C4A3$: 0.1~15%.
The raw materials of the cement clinker comprise iron raw materials, silicon-aluminum raw materials, calcium raw materials and gypsum,
The chemical composition of the raw materials is as follows 50%~64%CaO,15%~23%SiO2,3%~15%Al2O3,3%~12%Fe2O3,0.1%~24%SO3.
The iron raw material comprises any one or more of steel slag, iron tailings, laterite and red mud.
The silicon-aluminum raw material comprises any one or more of fly ash, coal gangue, bauxite, clay and sandstone.
The calcareous raw material comprises any one or more of limestone, marble, dolomite, steel slag and carbide slag.
The gypsum comprises any one or more of dihydrate gypsum, anhydrite, desulfurized gypsum and phosphogypsum.
The low-calcium silicate cement comprises, by mass, 95% -97% of low-calcium silicate cement clinker and 3% -5% of anhydrite.
The preparation method of the low-calcium silicate cement clinker is characterized by comprising the following steps:
(1) Pretreatment of raw materials
Drying the raw materials respectively, crushing and grinding the raw materials respectively to fully grind the raw materials;
(2) Premixing raw materials and tabletting
Uniformly mixing all the raw materials obtained by grinding in the step (1) to obtain raw materials;
(3) Calcination of clinker
And (3) calcining the raw material at a high temperature of 1300-1370 ℃, taking out the clinker after the calcining, quenching the clinker to room temperature, and cooling the clinker by a fan quenching to obtain the low-calcium silicate cement clinker.
The invention has the following effects:
(1) According to the invention, the content of C 2 S in the cement clinker is improved by designing high silicon content, so that the later-stage performance of the clinker is improved, and meanwhile, the early strength formed by rapid hydration of C 4A3 $ can make up for the problem of insufficient early hydration activity of the clinker caused by the improvement of the content of C 2 S, so that the cement has good performance development in the early, middle and later stages.
(2) According to the invention, by increasing the iron content in the clinker mineral composition, the iron phase mineral in the silicate clinker forms C 6AF2, the hydration rate is higher than that of C 4AF.C6AF2, the iron-containing ettringite is formed by hydration under the condition that gypsum exists, a compact structure is formed to supplement the gap in the cement slurry, the content of C 6AF2 is increased, the cement hydration slurry structure is more compact, and the erosion resistance and wear resistance of the clinker are improved.
Drawings
Fig. 1 is a schematic XRD detection of example 1.
Detailed Description
The present invention is described in detail below in connection with embodiments, examples of which are illustrated in the accompanying drawings, wherein like or similar reference numerals refer to like or similar elements or elements having like or similar functions throughout. The embodiments described below by referring to the drawings are illustrative only and are not to be construed as limiting the invention.
The raw materials and chemical compositions used in examples 1 to 3 are shown in Table 1.
TABLE 1 chemical composition of raw materials
Example 1:
The cement clinker design mineral composition is shown in table 2, raw materials are prepared according to the design mineral composition and the material balance principle, limestone is selected as a calcareous raw material according to the mass percentage, the proportion is 60.54%, bauxite and sandstone are selected as aluminous raw materials, the proportion is 6.55% and 10.99%, respectively, desulfurized gypsum is 0.94% and steel slag 20.98%, 1kg of uniformly mixed raw materials are weighed after being fully and uniformly mixed, and the raw materials are ground in a vibration mill until the screen residue of square holes of 0.075mm is lower than 5%, so that powdery cement raw materials are obtained.
Adding 8% of water (i.e. the water accounts for 8% of the mass of the raw material) into the powdery cement raw material, uniformly stirring, putting into a tablet press, pressing into a disc with the diameter of 235mm, and drying for 12h at 105 ℃. By adding water, the tablet is convenient to compress.
Taking out the materials, placing the materials into a muffle furnace which is preheated to 900 ℃ for calcination for 30 minutes, fully decomposing CaCO 3 in the raw materials into CaO, then transferring the CaO into an electric furnace at 1350 ℃ for heat preservation for 1 hour, taking out clinker, and rapidly cooling the clinker to room temperature by a fan to obtain a cooked material block.
And crushing the cooled cement clinker, and grinding the crushed cement clinker by using a ball mill until the specific surface area is 400+/-20 m 2/kg to obtain the cement clinker.
TABLE 2 mineral composition of Cement clinker (wt%)
The XRD pattern of the clinker in example 1 is shown in the attached figure 1, and a crystal diffraction peak of C 3S、C2S、C6AF2、C4A3 $ can be obviously observed in the XRD pattern, which shows that the clinker mineral formation condition is good.
Example 2:
The cement clinker design mineral composition is shown in table 3, and according to the design mineral composition and the material balance principle, raw materials including, by mass, 61.71% of limestone, 3.83% of bauxite, 12.50% of sandstone, 21.77% of steel slag and 0.19% of anhydrite are prepared, 1kg of uniformly mixed raw materials are weighed after being fully mixed, and the raw materials are ground in a vibration mill until the screen residue of square holes of 0.075mm is lower than 5%, so as to obtain powdery cement raw materials.
The method is characterized in that 8% of water by mass is added into powdery cement raw materials, the raw materials are uniformly stirred and pressed into compact raw material tablets and are sufficiently dried, and the purpose of the step is to promote solid phase reaction in the clinker formation process. The material was taken out and calcined at 900 ℃ for 30 minutes, then turned to 1350 ℃ for 1 hour, and the material was taken out and cooled rapidly to room temperature with a fan.
And crushing the cooled cement clinker blocks, and grinding the crushed cement clinker blocks by using a ball mill until the specific surface area is 400+/-20 m 2/kg to obtain cement clinker.
TABLE 3 mineral composition of Cement clinker (wt%)
Example 3:
The design mineral composition of the selected cement clinker is shown in table 4, and according to the design mineral composition and the material balance principle, raw materials including 63.33% of limestone, 6.59% of bauxite, 13.50% of sandstone, 14.71% of steel slag and 1.87% of anhydrite are prepared according to the mass percentage, 1kg of uniformly mixed raw materials are weighed and ground in a vibration mill until the screen residue of square holes of 0.075mm is lower than 5%, so as to obtain powdery cement raw materials.
Adding 8% of water into the powdery cement raw material, uniformly stirring, pressing into compact raw material tablets, and fully drying. The material was taken out and calcined at 900 ℃ for 30 minutes, then turned to 1350 ℃ for 1 hour, and the material was taken out and cooled rapidly to room temperature with a fan.
And crushing the cooled cement clinker blocks, and grinding the crushed cement clinker blocks until the specific surface area is 400+/-20 m 2/kg, thereby obtaining the cement clinker.
TABLE 4 mineral composition of Cement clinker (wt%)
Example 4:
Cement was prepared from the clinker prepared in examples 1, 2 and 3 in a ratio of clinker to anhydrite=95:5, labeled HFC1, HFC2 and HFC3, cement mortar strength was tested according to GB/T17671-1999 "cement mortar strength test method", the mortar ratio was 1:3, and a 40mm×40mm×160mm test-molded mortar test piece was used. Meanwhile, the reference cement properties, numbered p.o42.5, were compared to observe the properties of the novel clinker. The strength results are shown in Table 5.
TABLE 5
By way of comparison, the cement strengths in examples 1-3 of the present invention were higher than the strength of the P.O42.5 reference cement.
In the cement clinker, the C 3 S has high gelling activity, and the reduction of the content of the C 3 S directly leads to serious reduction of the strength performance of the cement. C 2 S has low early activity but better later strength. Calcium sulfoaluminate (C 4A3) has the characteristics of low calcium content and excellent early performance. By introducing sulfur into Portland cement to form C 4A3, the problems of insufficient early strength caused by the reduction of the content of C 3 S and the increase of the content of C 2 S can be effectively overcome. Even if C 4A3 is introduced, its content should be controlled as low as possible. In order to ensure stable development of clinker performance, the content of C 6AF2 and other iron phases with higher gelation activity is further regulated so as to realize industrialized wide popularization and application of the low-calcium silicate cement clinker.
In addition, iron phase minerals such as hexacalcium dialuminate (C 6AF2) have high strength and early strength, and have good effects in improving the toughness of Portland cement, sulfate corrosion resistance and the like. By increasing the content of C 6AF2 in the Portland cement, the advantages of the Portland cement in aspects of erosion resistance, wear resistance and the like can be remarkably exerted.
Aiming at the contradictory requirements of further calcium reduction, carbon reduction and high performance, the invention realizes the cooperative development of early and later performances of the clinker by simultaneously introducing C 4A3 $ and improving the content of C 2 S and high-gel iron phase, and simultaneously prepares the cement clinker with excellent performances such as wear resistance.
Claims (7)
Priority Applications (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN202311058401.8A CN116986830B (en) | 2023-08-22 | 2023-08-22 | Low-calcium silicate cement clinker, cement and preparation method thereof |
Applications Claiming Priority (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN202311058401.8A CN116986830B (en) | 2023-08-22 | 2023-08-22 | Low-calcium silicate cement clinker, cement and preparation method thereof |
Publications (2)
| Publication Number | Publication Date |
|---|---|
| CN116986830A CN116986830A (en) | 2023-11-03 |
| CN116986830B true CN116986830B (en) | 2025-09-16 |
Family
ID=88528350
Family Applications (1)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| CN202311058401.8A Active CN116986830B (en) | 2023-08-22 | 2023-08-22 | Low-calcium silicate cement clinker, cement and preparation method thereof |
Country Status (1)
| Country | Link |
|---|---|
| CN (1) | CN116986830B (en) |
Families Citing this family (3)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN117585920A (en) * | 2023-11-16 | 2024-02-23 | 西南科技大学 | Low clinker cementitious material and its preparation method and application |
| CN120058250B (en) * | 2025-04-23 | 2025-08-15 | 山东东华科技有限公司 | Cement clinker for high-speed rail and preparation method thereof |
| CN120328891A (en) * | 2025-05-16 | 2025-07-18 | 北京科技大学 | Multi-component solid waste cement clinker and preparation method thereof |
Citations (1)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN104788032A (en) * | 2015-04-09 | 2015-07-22 | 中国建筑材料科学研究总院 | Belite cement and preparation method thereof |
-
2023
- 2023-08-22 CN CN202311058401.8A patent/CN116986830B/en active Active
Patent Citations (1)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN104788032A (en) * | 2015-04-09 | 2015-07-22 | 中国建筑材料科学研究总院 | Belite cement and preparation method thereof |
Also Published As
| Publication number | Publication date |
|---|---|
| CN116986830A (en) | 2023-11-03 |
Similar Documents
| Publication | Publication Date | Title |
|---|---|---|
| CN107721214B (en) | A kind of high iron aluminate-Belite-sulfoaluminate cement clinker and preparation method thereof | |
| CN103613293B (en) | Minimum inflation high magnesium moderate heat cement, production method therefor and applications thereof | |
| CN111393047B (en) | A kind of high-speed iron belite cement and preparation method thereof | |
| CN116986830A (en) | Low calcium Portland cement clinker, cement and preparation method | |
| KR20160124896A (en) | Rapid-setting and hardening, high-belite sulfoaluminate cement clinker as well as application and production process thereof | |
| CN103373826B (en) | A kind of method utilizing iron tailings to prepare low-carbon cement clinker | |
| CN110078393B (en) | Method for preparing calcium sulfosilicate-sulphoaluminate cement at low temperature | |
| CN115849740A (en) | Dicalcium silicate-calcium sulfoaluminate-calcium sulfosilicate cement clinker and preparation process thereof | |
| CN112624640A (en) | Full-solid waste sulphoaluminate cement clinker for prefabricated parts and preparation method thereof | |
| CN111732352A (en) | Low-alkali cement clinker, low-alkali high-strength cement and preparation method thereof | |
| CN115159873A (en) | High iron phase-modified calcite high activity cement clinker and its preparation and application | |
| CN112374781A (en) | Steel slag modifier and preparation method and application thereof | |
| CN102936104B (en) | Method for preparing rapid hardening high-early-strength cement clinker | |
| CN110194604A (en) | Tricalcium silicate-sulphur calcium silicates-sulphate aluminium cement and its low temperature preparation method | |
| CN105000814A (en) | Processing method for preparing fast-hardening early-strength oil well cement with industrial waste slag | |
| CN119409436B (en) | A belite-aluminate mineral additive and its preparation method and application | |
| CN110590213A (en) | A kind of concrete expansion agent and preparation method | |
| CN113698116A (en) | Method for preparing high belite sulphoaluminate clinker by using lithium slag | |
| CN120208563A (en) | A kind of solid waste-based low-calcium clinker prepared at low temperature using industrial solid waste and method | |
| Alkhateeb | Chemical analysis of ordinary Portland cement of Iraq | |
| CN117401948B (en) | High-temperature sintered high-calcium sulphoaluminate red mud-based grouting material and its preparation method and application | |
| CN115368034B (en) | A self-powdering carbon-cured gelling material prepared from solid waste and its preparation method | |
| CN111892312A (en) | Method for utilizing multiple solid wastes in large mixing amount | |
| CN118125733A (en) | A kind of all-solid waste gelling material for compensating shrinkage of desulfurized gypsum and preparation method thereof | |
| CN118184188A (en) | High-belite sulphoaluminate cement clinker containing Q phase and C7MS4 and preparation method thereof |
Legal Events
| Date | Code | Title | Description |
|---|---|---|---|
| PB01 | Publication | ||
| PB01 | Publication | ||
| SE01 | Entry into force of request for substantive examination | ||
| SE01 | Entry into force of request for substantive examination | ||
| GR01 | Patent grant | ||
| GR01 | Patent grant |